European survey of enterprises on new and emerging risks (ESENER) (Luxembourg, 2010)
"The European Survey of Enterprises on New and Emerging Risks (ESENER) asks managers and workers' health and safety representatives about how health and safety risks are managed at their workplace, with a particular focus on the newer ‘psychosocial risks’, such as work-related stress, violence and harassment. This report presents an overview of the results from a first analysis of the data, which is drawn from 36,000 interviews carried out in 31 countries."